Removal of Zn(II) from aqueous solution by mangosteen shell powder - Wong J.K.; Oh M.L.; Chua K.H. (American Scientific Publishers, 2023)
Contamination of heavy metals in industrial effluents has become a concerned issue recently. In order to reduce the concentration of heavy metals in industrial effluents, biosorption method can be applied meet the discharge effluent standard. In this study, a typical Malaysian agricultural waste, mangosteen shell powder is used for the biosorption process in removing zinc from aqueous solution. In the experiment, a synthetic solution with known zinc concentration is tested with mangosteen shell powder at different contact time. This time dependent experiment for the removal of zinc ions showed that the binding of zinc ions to mangosteen shell powder is relatively fast if compared to rice husk ash, cocoa pod husk, green sands, groundnut shells, neem, carrot residues from the previous research. Equilibrium is reached in only 40 minutes contact time with the maximum percentage of zinc removal is 50%. Mangosteen shell powder achieved a maximum uptake capacity of 2.50 mg/g zinc ions. Another result is pH of the solution increased from 2.44 to 2.69 as the removal of zinc ion increased significantly over the contact time. Results show that mangosteen shell powder is a good adsorbent in removing zinc ions from aqueous solution. Mangosteen shell powder is a low cost adsorbent and environmentally friendly. Together with its efficiency as an adsorbent of zinc ions, it has high potential to be applied in waste water technology for treating inorganic effluents. 2017 American Scientific Publishers All rights reserved.